Local small business model from the Buyan Tamblingan Bali ecotourism destination program - I Gusti Bagus Rai Utama; I Wayan Ruspendi Junaedi; Ni Putu Dyah Krismawintari (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This research aims to examine the management of Buyan Tamblingan ecotourism destination in creating local small businesses. The research consisted of a survey, direct observation, interview, and literature study with documentation analysis. Data were collected through surveys and observations at the Buyan Tamblingan ecotourism destination. The motivation of the community involved in the ecotourism program in Buyan Tamblingan Motivation to earn money, motivation to gain knowledge about conservation, motivation to be optimistic that the ecotourism program will benefit the community, idealism about the importance of conservation, local community interest in self-reliance, promising income for the community and local community commitment. Opportunities expected by local communities from a strong ecotourism program in Buyan Tamblingan are the existence of facilities, the growing awareness of local communities, the existing natural beauty, and the arrival of tourists as opportunities for ecotourism management. The capacity of local communities to manage ecotourism in Buyan Tamblingan is a strong program because local communities commit to improving ecotourism management capabilities.Community involvement will increase if they have the opportunity to participate in ecotourism management, and for that better ecotourism management skills are needed. If they are motivated, have the opportunity to participate, and are able to participate, then they will be able to create small business opportunities related to ecotourism programs.